A HISTORICAL ANALYSIS OF THERMAL COMFORT: THE EVOLUTION OF VENTILATION SYSTEMS AT THE ROYAL VICTORIA HOSPITAL, BELFAST - Farahdilla, Suci (Arsitekno, 2025)
The Royal Victoria Hospital in Belfast, founded in the late 18th century, marks a pivotal moment in the evolution of hospital design and healthcare delivery. This paper traces the hospital's development from its origins as the General Dispensary to its transformation into a modern medical facility. Central to this evolution was the architectural vision of William Henman, who introduced the plenum system of mechanical ventilation”an innovative and pioneering approach at the time. This study investigates the impact of Henmans design on thermal comfort and air quality within the hospital, focusing on both the challenges and successes of implementing such a system in the early 20th century. Through the analysis of historical documents and architectural plans, this research offers insights into the relationship between hospital design, patient care, and environmental control. The findings highlight the critical role of thermal management strategies in healthcare architecture and offer lessons for contemporary hospital design in the pursuit of enhanced patient outcomes.